Routing in Vehicular Ad Hoc Networks: Main Characteristics and Tendencies - Joilson Alves Junior; Emilio C. G. Wille (Journal of Computer Networks and Communications)
The message routing in vehicular ad hoc networks (VANETs) is an attractive and promising area for research. These networks do not have a central coordination, the nodes are mobile, and the topology is highly dynamic, making the routing process a big challenge, since it is responsible for ensuring message delivery with small overhead and delay. In the literature, there are several routing protocols that can be used in VANETs; in this way, the main objective of this work is to classify, discuss, and compare such protocols through a review of research in this field. The protocol classification is based on the following criteria: type of architecture and mode of operation. Moreover, this work emphasizes the potential of the application of bioinspired and bus-based techniques in the routing problem solutions, which has been revealed as a main tendency nowadays. Bioinspired routing protocols are based on the behavior of entities in the nature, and they are meant to work in a distributed mode, using mobile agents to find routes with specific features. In a parallel line of research, the differentiated behavior of urban transport vehicles suggests that a system that makes use of buses to create a communication infrastructure can perform better when compared to a system that does not distinguish between vehicles.